2009
DOI: 10.1179/dfi.2009.011
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Passive Piles Failure in Open Excavation

Abstract: This paper presents a case study in West Malaysia for passive piles failure in very soft marine clay in open excavation. In this particular case, the thickness of the very soft marine clay ranges from 5 m to 7 m (16 ft to 23 ft) from the ground surface. Preliminary site investigation reported SPT 'N' value of zero for the very soft marine clay. The design was based on a deep foundation utilizing driven piles to support the superstructure. During pile cap construction, the piles were subjected to uncontrolled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…However, under various conditions of stress, it behaves in a heterogeneous pattern i.e., during loading, unloading, and reloading state conditions. Moreover, it exhibits non-linear behavior pattern below the plastic limit with stress-dependent stiffness [ 1 ]. A good understanding of all this complexity states and the knowledge of the soil behavior is important in geotechnical analysis and design of geostructures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under various conditions of stress, it behaves in a heterogeneous pattern i.e., during loading, unloading, and reloading state conditions. Moreover, it exhibits non-linear behavior pattern below the plastic limit with stress-dependent stiffness [ 1 ]. A good understanding of all this complexity states and the knowledge of the soil behavior is important in geotechnical analysis and design of geostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Second is the experimental evaluation of the models with respect to their suitability to fit experimental data from a variety of available tests and the ease of the determination of the material parameters from standard test data. The final criteria are the numerical and computational evaluation of the models with respect to the facility which can be implemented in computer calculations [ 1 ]. However, the objective of this paper is to extensively review classical and advanced soil constitutive models, which have been implemented by several geotechnical software, to present a better understanding to young modelers in their projects, and also identify the applicability and limitation swifter.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kok S.T (2009), there are three common methods for researching about the effect of excavation to the nearby pile foundation: The Finite element, the centrifuge test and the field test [1,4]. Poulos & Chen (1996) did analysis by using of the finite-element method analyze the response of piles due to unsupported excavation induced lateral soil movement in clay [2].…”
Section: Introdutionmentioning
confidence: 99%
“…The impact is significant, particularly for piles constructed in soft clay. There have been several instances where the existing pile foundations were affected or damaged because of adjacent excavation, e.g., Amirsoleymani (1991), Finno et al (1991), Chu (1994), and Kok et al (2009). To estimate the excavation-induced pile response, empirical and numerical studies were conducted Chen 1996, 1997;Chow and Yong 1996;Guo 2003;Ong et al 2009;Zhang et al 2011).…”
mentioning
confidence: 99%
“…For the field tests, Finno et al (1991) and Goh et al (2003) reported the performance of pile groups and single piles adjacent to a deep supported excavation, respectively. Thasnanipan et al (1998) and Kok et al (2009) presented case studies of pile failure associated with open excavations in Bangkok soft clay and West Malaysia marine clay, respectively. The results of D r a f t these researchers lay a foundation for in-depth study.…”
mentioning
confidence: 99%